Effects of walking distance over robot-assisted training on walking ability in chronic stroke patients. (November 2020) - Nankaku, Manabu; Tanaka, Hiroki; Ikeguchi, Ryosuke; Kikuchi, Takayuki; Miyamoto, Susumu; Matsuda, Shuichi
Highlights: Walking after stroke is important for independent ADL and social activities. HAL system was an effective for maximizing gait speed in chronic stroke patients. Walking distance over robot training is related with improvement of outcomes. Abstract: An understanding of the dose-response during training is important to identify the rehabilitation programs to obtain the improvement in chronic stroke patients. The purpose of this study was to determine whether distance-dose (distance walked across all sessions) during robot-assisted training affects the change of walking speed and distance in chronic stroke patients after intervention. Fifteen chronic stroke patients were enrolled in this study. The patients performed 8 gait training sessions using the Hybrid Assistive Limb (HAL) for 3 weeks. Gait speed, stride length, cadence, and 2-minute walk test (2MWT) were measured before and post-intervention. Total walking distance (distance walked across all sessions) in individual patients were also measured. Gait speed, stride length, cadence, and 2-minute walk test (2MWT) improved significantly after training. The average of walking distance for 8 sessions in individual patients was 3793.3 ± 2105.3 m. Moreover, the change of gait speed (r = 0.53) and 2MWT (r = 0.70) were positively correlated with the walking distance during 8 sessions. This study of finding demonstrated that greater total distance walked over all sessions of training using the HAL is directly associated with the better walking outcomes in patients with chronic stroke. Further researches with a larger number of patients and a control group are needed to quantify the study results more precisely.